DEVELOPMENT OF STUDENTS' LANGUAGE SKILLS IN ENGLISH LANGUAGE TEACHING - Obidova Mohitabon Elyor qizi, Ayatov Raximberdi Ibragimovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The development of language skills among students in the field of teaching English is a critical area of study, essential for effective communication, academic achievement, and professional success in an increasingly globalized world. This article explores various facets of language skills development—listening, speaking, reading, and writing—in the context of English language teaching (ELT). It examines pedagogical approaches, cultural influences, technological advancements, and the integration of skills to provide a comprehensive understanding of how educators can enhance students' proficiency in English.